Functional analysis of a splice site mutation in BABRG2 gene and its effect on GABAA receptor - Kaplan, Öyküm. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Epilepsy is a group of diseases produced by non-controlled discharge of neurons affecting more than 2% of the population and some forms include genetic determinants. The principal group of inherited epilepsy is Genetic Generalized Epilepsies (GGE) and Childhood Absence Epilepsy (CAE) is a common subtype of GGE. Gamma-Aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the mammalian brain. It acts through two classes of receptors: GABAA and GABAB receptors. Impairment of GABAergic transmission by genetic mutations cause epileptic seizures. GABAA receptor, gamma 2 which is located on 5q34, is encoded by GABRG gene. Besides mutations which are in coding region in GABRG2 gene, mutations in intronic sites of the gene are also observed. It has been shown that a T-G transversion (IVS6+2T-G) mutation altered the GABRG2 intron 6 splice donor site sequence, activated a cryptic splice site and generated partial intron retention. The aim of this study was to investigate the effect of an other splice site variant of GABRG2 gene detected in a CAE patient on GABAA receptor. Scores of splice site tools showed that this mutation could create cryptic splice site. By site directed mutagenesis, the known mutation was created and cloned with the GABRG2 variant in the patient by creating minigenes. After transfection, expressions were checked by RT- PCR. Under similar experimental conditions while the splicing defect of the known mutation was observed, GABRG2 splice site variant in the CAE patient had no effect on splicing suggesting that it was a silent variant of the gene.
Keywords: Epilepsy.